PENGEMBANGAN POTENSI KELOKALAN DESA KARANGPATIHAN DALAM PENGEMBANGAN WISATA BERBASIS MASYARAKAT - Wardhani, Windi Novia Ratri; Pratiwi, Ratih - (STIE Pelita Nusantara, 2024)
Engagement with the community is not only an implementation of the third pillar of the Tridharma of Higher Education but also a strategic step to enhance the execution of the pillars of education, research, and community service. The village of Karangpatihan, previously known as the 'village of the intellectually disabled' due to a high number of residents with intellectual disabilities, has undergone positive changes through collaborative efforts with Rumah Harapan. Through this initiative, our goal is to develop the local potential of the village by supporting training programs in skills development, local product marketing, and community-based tourism promotion. In this context, we conducted a mini-workshop titled